Intraoperative Intermittent Blocking of the Common Iliac Arteries in Cases of Placenta Percreta without the Use of Fluoroscopy - Heinze, S.; Filsinger, B.; Kastenholz, G.; Schröder, R. J. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Background: The number of patients with placenta accreta, percreta and increta is increasing. The morbidity and mortality are higher mostly due to hemorrhage. Therefore, new methods to reduce the risk of severe bleeding are necessary.Methods: Three patients were treated in collaboration by obstetricians, urologists, anesthesiologists, and radiologists. An MRI of the pelvis was performed and the diameters and lengths of the iliac arteries were measured to avoid fluoroscopy during the preoperative placement of catheter balloons into the iliac arteries. During the operational procedure the balloons were inflated and deflated depending on the operative site and the occurrence of bleeding.Results: In comparison to the literature, severe bleeding was clearly reduced. No complications of the intervention were observed.Conclusion: The presented method to reduce severe bleeding might represent significant progress in the management of abnormal placenta implantation. Nevertheless, further controlled studies are needed in order to establish evidence-based recommendations.Key Points:• Reduction of perioperative hemorrhage in cases of placenta accreta, percreta, and increta.• A preinterventional MRI of the pelvis allows measurement of the illiac arteries so that the fetus is not exposed to radiation.• The short occlusion time (under the nominal pressure of the balloon) of the common iliac arteries reduced interventional complications.Citation Format:• Heinze S, Filsinger B, Kastenholz G et al. Intraoperative Intermittent Blocking of the Common Iliac Arteries in Cases of Placenta Percreta without the Use of Fluoroscopy. Fortschr Röntgenstr 2016; 188: 1151 – 1155
Keywords: placenta accreta/percreta; iliac artery ballon occlusion; uterine hemorrhage; cesarean section